O Método de Formação Sequência Fedathi: o bom formador sob a perspectiva da formação Fedathi generalizada - Felício, Milínia Stephanie Nogueira Barbosa (2024)
Many basic education teachers still use traditional practices in their way of teaching, in which they focus on the amount of information that the student can capture, aiming for cognition, but not giving enough time for the student to mature. Based on movements of change in the classroom of a basic education researcher from the state education system, after the Fedathi Project course offered by the Laboratório de Pesquisa Multimeios (Multimedia Research Laboratory) of the Federal University of Ceará, we sought to understand what contributions in terms of changes in teachers' ideas and practices and continued training outlined with the Fedathi Sequence research methodology and its conceptions can provoke in the teacher, resulting in Generalized Fedathi Training. The purpose was to expand to other areas beyond Mathematics with which the Fedathi Sequence is allied in its origin. Seeking, therefore, to systematize the Generalized Fedathi Training outlined by a Fedathi Sequence Training Method incorporated into the training practices of the Multimedia Research Laboratory, which would indicate a culture of reflection on methodological teaching guidelines and change of practice among subjects that also impact the immersed trainer. The research is qualitative in nature, a case study designed with action research, as it favors greater freedom for interference and transformation of participants. The main results were the systematization of the Fedathi Sequence Research Method, identified and tested in the application of Generalized Fedathi Training, built in three stages: Awareness, Reflection and Change (Position Taking, Maturation, Solution and Proof) and Sustainability. The change processes were identified in the dialogues of the training actors, through Bardin's content analysis.